PEMBERDAYAAN MASYARAKAT DALAM PENGEMBANGAN KEMANDIRIAN MASYARAKAT - Suryo, Herning (Transformasi, 2016)
Community empowerment in fact intended to form an independent society not onlyeconomically but also of other aspects such as politics, education, social or things related topeople's lives. With the expected empowerment of communities to apply independently, have astrong position for itself when the situation does not favor when a policy only benefit certaingroups. Not an easy matter to change the situation of helplessness into a society that has nopower because there are various constraints or factors inhibiting, people who had long beenmired in shackles without power formed into an apathetic public, irresolute, lazy and did nothave the confidence to such a change toward better direction.Key Word: community, empowerment, independent